Złożone leczenie wysiękowej postaci zwyrodnienia plamki związanego z wiekiem - Figurska, Małgorzata; Wierzbowska, Joanna; Robaszkiewicz, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Therapeutic options in active exudative age-related macular degeneration (AMD) are following means used to destroy the choroidal neovascularization (CNV) lesion: laser photocoagulation, radiotherapy, transpupillary thermotherapy, photodynamic therapy (PDT) or removal of neovascular membrane through vitreoretinal surgery. Another possibility is to suppress the development of neovascularization through intravitreal administration of anti-VEGF agents: ranibizumab, bevacizumab (off-label), sodium pegaptanib or steroids (off-label). The aim of this paper is to present the early phase of treating exudative AMD with combined therapy: photodynamic therapy with intravitreal ranibizumab injection. Material and methods: Our observation is based on three clinical cases. Observations are being carried out on larger patient groups according to the treatment scheme presented in this paper. Results: In the three cases described one PDT procedure and the saturation phase of three ranibizumab injections allowed a significant improvement in visual acuity and closure of CNV leakage confirmed by fluorescein angiography (FA) and optical coherence tomography (OCT). Treatment is being continued according to AMD activity: next PDT in case of leakage in FA, another ranibizumab injection according to PRONTO study reinjection criteria. Conclusions: The pathomechanism of exudative AMD confirms reasonability of combined treatment. Considering the stages of neovascularization in exudative AMD, VEGF inhibition combined with PDT has a synergistic action and increases the effectiveness of both therapies alone. Large clinical studies (FOCUS) show that combined therapy reduces the number or required PDT procedures. In combined therapy modification of PDT parameters should be considered: reduction of energy and laser exposure time.